The Geography of Migration in the Texts and Places of Poet Bushra Al-Bustani Some of Her Texts as Examples - Abbas, Assist.Lect. Riyam Shalal; Fazea, Assist.Lect. Samer Rahim (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2026)
In the spaces of Bushra Al-Bustani’s poetry, migration becomes a river flowing between the banks of existence and non-existence. The journey here is not a transition between cities, but a constant crossing in the corridors of memory and language. Baghdad then becomes a shadow haunted by water, and the sea becomes a poem yet to be written. With words that bleed salt and light, Al-Bustani weaves a poetic map where place is a moaning woman and language is a harbour in which the poet’s name drowns. Each text is a satire on stability and a hymn to departure as existential salvation. She writes with the blood of both the wolf and the dove, and the poem becomes a journey between the wound of reality and the splendour of symbolism.This research aims to analyse the manifestations of the concept of "journey" in the poetry of Bushra al-Bustani as a complex semantic structure that transcends spatial displacement to cognitive and existential dimensions. The study adopted an integrative analytical approach to examine the triad (place-language-self) through examples from her poetry collections. In Al-Bustani’s work, migration is an aesthetic project that reshapes poetic geography, where place is transformed into a symbolic feminine entity (mother/exile/mirror) and language represents a dynamic space of migration, dissolving the boundaries between the real and the symbolic, as in her simile "language is a river that knows no banks." The existential dimension is manifested in the conception of the poetic text as a "satire of residence," where departure becomes an expression of rebellion against the stability of meaning and identity. The study offers a qualitative addition to the reading of modern Arabic poetry by linking spatial displacement with ontological questions, highlighting how poetry transforms geography into an open semantic field.